Four decades of developmental dysplastic hip screening according to Graf: What have we learned? - Walter, Sebastian G.; Ossendorff, Robert; Yagdiran, Ayla; Hockmann, Jan; Bornemann, Rahel; Placzek, Sonja (Frontiers in Pediatrics, 2022)
Purpose Sonographic hip examination according to Graf is widely accepted standard for diagnosing developmental dysplastic hips (DDH) but it is criticized for alleged intra- and interobserver variations. This review was conducted to evaluate whether objective quality criteria according to the Graf method are fulfilled within scientific literature. Methods A systematic literature search on Pubmed was performed using the search string: [(DDH) OR (Hip dysplasia)] AND (Graf). Studies suitable by title, abstract, manuscript, containing an image of sonographic hip examination and online accessibility were included into analysis. Results 131 studies were included into final analysis. Only 68 (51.9%) presented correct sonographic images according Graf’s criteria. 98 (74.8%) studies plotted alpha-angles (angle between bony roof line and base line) but only 85 (64.8%) studies beta-angles (angle between cartilage roof line and base line). Studies were contributed from 25 countries. Conclusion Assumingly, skepticism regarding the Graf method is based on user errors and insufficient application of the Graf quality assessment algorithm resulting in high intra- and interobserver variations. When performed correctly, the Graf method is of high diagnostic value.